A real-world disproportionality analysis of FDA adverse event reporting system (FAERS) events for denosumab - He, Yue; Zhang, Rong; Shen, Huarui; Liu, Yingqi (Frontiers in Pharmacology, 2024)
Background Denosumab is authorized to treat several diseases, including cancer and bone disorders. Nevertheless, its use in clinical practice has been affected by safety concerns. The work retrospectively investigated adverse events (AEs) of denosumab to better understand toxicities. Methods The FAERS data base data from Q1 of 2010 to Q3 of 2023 was chosen. The definition of Medical Dictionary for Regulatory Activities (MedDRA) was dependent on preferred terms (PTs) and system organ class (SOCs). Following the removal of duplicate reports, a disproportionality analysis was conducted to identify safety signals through the calculation of reporting odds ratios (ROR). Results During the reporting period, 130611 denosumab-related cases were identified; 670 pTs with a substantial disproportionality were retained. The connective and musculoskeletal tissue disorders, poisoning, injury, and procedural complications, as well as medical and surgical procedures, were among the important SOCs that satisfied the criteria. Reports at PT levels including off-label use, death, osteonecrosis of the jaw, arthralgia, and pain in extremities were determined. Severe consequences in terms of life-threatening injuries and death accounted for 841 and 19704 cases, respectively of the reported cases. Conclusion These findings underscore the critical importance of pharmacovigilance and are consistent with established clinical observations. Notably, osteonecrosis of the jaw, arthralgia, pain in extremities, back pain, myalgia, and bone pain were identified as the most prevalent risk signals associated with denosumab.